Pilar Ekonomi Hijau melalui Ekspresi Budaya Tradisional: Model Perlindungan Sendang Kun Gerit untuk Penguatan BUMDes Wisata di Jawa Tengah - Triyono Adi Saputro; Awalia Rina Rahmawati (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study examines the protection model of Traditional Cultural Expression (TCE) of Sendang Kun Gerit as a pillar of green economy in strengthening tourism Village-Owned Enterprises (BUMDes) in Central Java. Sendang Kun Gerit is a sacred water spring rich in cultural and ecological values in Sragen Regency that has not yet received adequate legal protection. Through a juridical-empirical approach with  field observations, and documentation studies, this research analyzes three dimensions: (1) the existing legal framework for TCE protection in Indonesia; (2) the potential of Sendang Kun Gerit as a tourism asset based on local wisdom; and (3) the BUMDes integration model in TCE governance for green economy development. The findings reveal that Sendang Kun Gerit has significant but underutilized potential as an ecotourism destination due to weak institutional governance and the absence of legal protection for traditional cultural expression. This study recommends a Tri-Pillar Conservation-Commercialization-Community model that integrates TCE protection, BUMDes empowerment, and green economy principles as a holistic solution for community based cultural heritage management in Central Java